The Cambridge introduction to Herman Melville - Hayes, Kevin J (Cambridge University, 2013)
Despite its indifferent reception when it was first published in 1851, Moby-Dick is now a central work in the American literary canon. This introduction offers readings of Melville's masterpiece, but it also sets out the key themes, contexts, and critical reception of his entire oeuvre. Kevin J. Hayes provides comprehensive information about Melville's life and works in an accessible book that will be essential for students beginning to read this important